The impact of labour legislation on selected small firms in Mbombela (Nelspruit) - Dlamini, Sikhulile Blessing (Rhodes University, Faculty of Humanities, Department of Sociology, 2021)
This study uses the theoretical framework of industrial relations pluralism, to study and analyse the impacts of labour legislation on six small firms (employing less than 50 workers) based in Mbombela (formerly Nelspruit), Mpumalanga province, South Africa. The analysis is based on the viewpoints of six managers and how they see the impacts of labour legislation on their respective firms. The analysis is aided by utilising theory and literature to make sense of the manager perspectives on the topic. Also, utilising a qualitative research design to collect and analyse the data, the study presents diverse findings in terms of how the participants perceived and experienced certain types of legislation. Some managers believed that the benefits of labour legislation outweighed the costs. While others believed the exact opposite. At an overall level, the study revealed that most of the participants were not as severely affected by labour legislation as might be expected; given the scarcity of resources in most small firms. This was partly because of various coping strategies and practices (mostly involving the use of informal procedures) that were adopted by the firms. Also, some small firms who aimed at expanding their businesses strategised to adopt some formal procedures and practices in order to easily absorb labour legislation and subsequently mordenise their businesses in the process. While a few firms persisted with more informal customs as they appeared cost-effective and necessary in their particular market positioning.
Keywords: Labor laws and legislation -- South Africa; Small business -- Law and legislation-- South Afric; Small business -- South Africa -- Mbombela -- Case studies